Student’s perspectives about their learning profile before and after Covid-19 - André Moura; Amândio Graça; Ann MacPhail; Paula Batista (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Changes in educational paradigms have affected the understanding of how individuals learn. The emergence of Covid-19 has created unprecedented disruption in the education systems. This study attempts to analyse students' perceptions of their learning profile before and after Covid-19, using two different cohorts of students from five schools. Participated in October 2019 (first application) 369 students, and in November 2021 (second application) 294 students. These are students of two educational cycles: grades 7-9 and 10-12. The Effective Lifelong Learning Inventory questionnaire has seven dimensions: ‘moving and learning’, ‘critical curiosity’, ‘making sense’, ‘creativity’, ‘learning relationships’, ‘strategic awareness’, ‘resilience’; and it was administered to understand how students self-assess their learning profile. Descriptive and inferential statistics were calculated to analyse the data and detect possible differences in the learning profiles. The results show that students in grades 7-9 seem to have been the most affected by Covid-19 (means were statistically significant in all dimensions except ‘resilience’) when compared to students in grades 10-12 (statistically significant only in ‘critical curiosity’, ‘learning relationships’ and ‘meaning making’ dimensions). In conclusion, the learning profiles have changed between the applications in both cycles. A higher percentage of students rated themselves worse in almost all dimensions in the second application. However, the increased autonomy during Covid-19 could explain the average increases in 'resilience' in grades 7-9 and 'creativity' in grades 10-12 from the first to the second application.